2019
DOI: 10.1038/s41598-018-37014-7
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Cochlear Implant Outcome in Children with Cochlear Nerve Deficiency

Abstract: The outcome of cochlear implantation (CI) in patients with cochlear nerve deficiency (CND) is variable, resulting in a wide range of speech perception performance, from degrees of environmental sound perception to conversation without lip-reading. Twenty-five cochlear implantees with CND were enrolled retrospectively to determine the factors correlated with CI outcome in patients with CND and to develop a predictive model for CI outcome. CI outcome was evaluated using the Categories of Auditory Performance (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 57 publications
3
31
1
2
Order By: Relevance
“…Our prospective data showed that two (50.0%) of the four probands who do not carry OTOF variants based on the genotyping kit had bilateral CND based on IAC-MRI. Previous studies have also shown that CND is significantly associated with poor speech intelligibility or perception after cochlear implantation, posing potentially limited effectiveness and uncertain cost-benefits [ 31 , 32 ]. In addition, previous studies suggested that the sensitive period for successful CI outcomes for children with OTOF -related DFNB9 may be narrower than that for those with SLC26A4 - and GJB2 -related deafness [ 14 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our prospective data showed that two (50.0%) of the four probands who do not carry OTOF variants based on the genotyping kit had bilateral CND based on IAC-MRI. Previous studies have also shown that CND is significantly associated with poor speech intelligibility or perception after cochlear implantation, posing potentially limited effectiveness and uncertain cost-benefits [ 31 , 32 ]. In addition, previous studies suggested that the sensitive period for successful CI outcomes for children with OTOF -related DFNB9 may be narrower than that for those with SLC26A4 - and GJB2 -related deafness [ 14 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies reported a variable CI surgery outcome among patients based on types of inner ear anomalies [2,4,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Several authors reported that patients who have mild anomalies such as EVA and IP II have a better outcome than patients who have severe malformations such as a common cavity [4,[24][25][26][27][28]31]. Nevertheless, Tay et al has concluded that the outcome of patients who have an absent cochlear nerve, electrode folding and underlying neurological disorders is poor [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…-Xác định dây TK ốc tai -tiền đình chung khi chỉ thấy dây TK VIII mà không có sự phân chia thành các nhánh TK tiền đình, TK ốc tai. Trên thực tế nhiều trường hợp mặc dù không có dây TK ốc tai trên CHT nhưng BN vẫn có đáp ứng với kích thích âm thanh khi đánh giá thính lực, thậm chí chỉ nghe kém ở mức độ nhẹ hoặc trung bình [6]. Điều này cũng thấy trong nghiên cứu của chúng tôi, có tới 11/34 tai (32,4%) thiểu sản hoặc bất sản TK ốc tai có sóng V trên ABR.…”
Section: Phương Pháp Nghiên Cứuunclassified
“…Điều này cũng thấy trong nghiên cứu của chúng tôi, có tới 11/34 tai (32,4%) thiểu sản hoặc bất sản TK ốc tai có sóng V trên ABR. Jae Joon Han nghiên cứu 25 BN có bất thường dây TK ốc tai sau cấy OTĐT cho thấy những BN không đáp ứng với ABR có thang điểm đánh giá thính lực thấp hơn một cách có ý nghĩa so với BN có đáp ứng với ABR [6].…”
Section: Phương Pháp Nghiên Cứuunclassified